Indian J Pharm Sci 2020
DOI: 10.36468/pharmaceutical-sciences.675
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective, Antioxidant and Cytotoxic Potential of Aloe niebuhriana Latex Extract from Yemen

Abstract: The aim of this study was to quantify the total phenolic content of Aloe niebuhriana latex extract and validate its antioxidant, hepatoprotective and cytotoxic activity. The total phenolic content of the extract was estimated spectrophotometrically using Folin Ciocalteu method. The antioxidant activity of the latex extract was determined using 2,2-diphenyl-1-picrylhydrazyl free radical scavenging assay. Paracetamolinduced hepatotoxicity rat model was used to evaluate the hepatoprotective activity of the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…The present study also found that FT3 or FT4 was decreased in patients with erythrodermic psoriasis, and the proportion of patients with normal TSH was as high as 42.59% [16]. This may be due to diffuse erythema and repeated shedding of scales in erythrodermic psoriasis patients, resulting in the loss of large amounts of water, protein, and other nutrients, causing water and electrolyte disturbances, metabolic abnormalities such as hypoproteinemia, and severe symptoms of systemic wasting.…”
Section: Discussionsupporting
confidence: 69%
“…The present study also found that FT3 or FT4 was decreased in patients with erythrodermic psoriasis, and the proportion of patients with normal TSH was as high as 42.59% [16]. This may be due to diffuse erythema and repeated shedding of scales in erythrodermic psoriasis patients, resulting in the loss of large amounts of water, protein, and other nutrients, causing water and electrolyte disturbances, metabolic abnormalities such as hypoproteinemia, and severe symptoms of systemic wasting.…”
Section: Discussionsupporting
confidence: 69%
“…These results were in agreement with other study that reported weak cytotoxicity of other Aloe species. Moharram et al [18] reported that Aloe niebuhriana latex extract exhibited a weak cytotoxicity effect against MCF-7, HepG2 and HCT-116 cancer cell line. Fox et al [19] also reported that Aloe vera, Aloe ferox and Aloe marlothii exhibited weak cytotoxicity effect towards the HaCaT cells using MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…Aloe niebuhriana showed weak cytotoxic activity towards MCF-7, human liver cancer HepG2 and HCT-116 cell lines. However, studies of other Aloe species have shown a similar cytotoxic effect towards normal human keratinocytes ( Moharram et al., 2020 ). Hence, this cytotoxic effect may not be restricted to cancer cells.…”
Section: Anticancer Properties Of Latex-bearing Plant Extractsmentioning
confidence: 94%